The structure of zooplankton and its relationship to marine conditions in the northerm Colombian Caribbean (2024)
During the dry and rainy seasons of 2019, two research cruises were conducted to determine the composition, abundance, biomass, and diversity of the zooplankton assemblage, and its relationship with the water conditions, along the northern Colombian Caribbean coast. The 21 sampling locations were situated in two of the Colombian Caribbean’s physicochemical provinces: Magdalena-Ciénaga Grande de Santa Marta (Mag-CGSM) and Parque Nacional Natural Tayrona-Guajira (PNNT-Gua). At each location, samples were collected using a bongo net through circular surface tows. Eighty-seven taxa (72 families and 15 morphotypes) were recorded, with the highest number of families found in Mag-CGSM during the dry season. The highest abundance and biomass were observed in PNNT-Gua during the rainy season while the highest species diversity was recorded in PNNT-Gua during the dry season. Conversely, the lowest species diversity was detected in the same province during the rainy season, coinciding with an increase in dominant families. This increase in dominance resulted in a decrease in uniformity. The spatiotemporal dynamics of the assemblage were most closely associated with the dissolved oxygen and salinity, highlighting their crucial role in shaping the structure of the zooplankton community.